Analisis Faktor Kinerja Organisasi Bumdesa Muncul Sari Aji - Gunawan, Ketut (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Bumdesa Muncul Sari aji experienced problems of low organizational performance. This is indicated by the high number of credit congestion implemented. Based on these problems, it is interesting to know the various factors that affect the performance of the Bumdesa Muncul Sari Aji organization. This study aims to determine the influence of Individual Factors, Psychological Factors and Organizational Factors on the Organizational Performance of Bumdesa Muncul Sari Aji. Data was collected through a survey using questionnaires on 19 respondents. Individual factors include: ability, skills and work experience; Psychological factors include: perception, personality, motivation and job satisfaction; Organizational Factors include: Organizational Structure, resources, job design, reward system and leadership and Organizational Performance includes: Sales Growth; Capital Growth; workforce growth; profit growth; Market Growth and Productivity. The data obtained has met the requirements for liquidity and reliability. The results of the analysis show that: 1). There is a positive and significant influence of Individual Factors on Organizational Performance; 2). There is a positive and significant influence of Psychological Factors on Organizational Performance; 3). There is a positive and significant influence of Organizational Factors on Organizational Performance; 4). There is a simultaneous influence of Individual Factors, Psychological Factors and Organizational Factors on Organizational Performance; 5). Organizational Factors are the most dominant factors affecting organizational performance.